Estimation of Lead and Other Elements in Rocks, Soil and Silt Samples of Fluorite Mine Area of Chandidongri, Distt. Rajnandgaon in Chhattisgarh - Biswas, S.N.; Lata Mohabey, Hem; Naik, M.L. (Asian Journal of Chemistry, 2010)
Rock, soil and silt samples were collected from fluorite mine area and non-mineralized area of Chandidongri (Chhattisgarh) and were analyzed for fluoride and other metals, viz., lead, iron, aluminium, zinc, copper, etc. Some rock samples had very high percentage of lead, zinc, manganese, calcium and flouride, while others had very low concentration of the same. Thus rock samples exhibited much variation in composition while lesser variation in the concentration of the metals estimated was noticed in soil and silt. The experimental area being fluoride mineralised area, fluoride was present in all the samples collected.